(untitled) (LEGAL DIALOGICA, 2025)
This study aims to examine and analyze the application of the Passala customary sanction in the Ammatoa Kajang customary law community of Bulukumba Regency. This study aims to understand and analyze the process of implementing customary sanctions within the Ammatoa customary law area. This study utilizes an empirical legal research methodology, which is essentially a combination of normative legal principles with the addition of empirical elements. The results of this study indicate that the Legal Review of the Implementation of Passala Customary Sanctions in the Ammatoa Kajang Customary Law Community of Bulukumba Regency is related to the process of implementing Passala customary sanctions which are consistently applied by customary leaders as an effort to resolve conflicts and restore social balance. The form of Passala sanctions varies, ranging from payment of fines in the form of goods or money, to certain customary rituals, depending on the type of violation and its severity. Legally, the implementation of Passala customary sanctions falls within the realm of recognition and protection of customary law, as stipulated in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia and various other laws and regulations. However, coordination and harmonization between customary law and positive law remain crucial issues, particularly in cases involving criminal or broader civil matters. Recommendations for research on the effectiveness of Passala customary sanctions in maintaining local wisdom and the social system of the Ammatoa Kajang community. It is crucial for the government and other stakeholders to better understand and support the existence of these customary sanctions, while ensuring that their implementation aligns with human rights principles and the national legal system. This study recommends strengthening collaboration between customary institutions and formal law enforcement institutions to create synergy in law enforcement and justice for indigenous communities. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis tinjauan teìrhadap peìneìrapan sanksi adat passala pada masyarakat hukum adat ammatoa kajang kabupateìn bulukumba, untuk meìngeìtahui dan meìnganalisis proseìs peìneìrapan sanksi adat yang teìrjadi dalam Kawasan hukum adat ammatoa. Peìneìlitian ini meìnggunakan meìtodeì peìneìlitian hukum eìmpiris pada dasarnya ialah peìnggabungan antara peìdeìkatan hukum normativeì deìngan adanya peìnambahan seìbagai unsur-unsur eìmpiris. Hasil peìnlitian ini meìnujukkan bahwa Tinjauan Hukum Teìrhadap Peìneìrapan Sanksi Adat Passala Pada Masyarakat Hukum Adat Ammatoa Kajang Kabupateìn Bulukumba adalah teìrkait proseìs peìneìrapan sanksi adat Passala diteìrapkan seìcara konsisteìn oleìh peìmangku adat seìbagai upaya peìnyeìleìsaian konflik dan peìmulihan keìseìimbangan sosial. Beìntuk sanksi Passala beìrvariasi, mulai dari peìmbayaran deìnda dalam beìntuk barang atau uang, hingga ritual adat teìrteìntu, teìrgantung pada jeìnis peìlanggaran dan tingkat keìparahannya. Seìcara yuridis, peìneìrapan sanksi adat Passala beìrada dalam ranah peìngakuan dan peìrlindungan hukum adat seìbagaimana diatur dalam Pasal 18B ayat (2) UUD NRI 1945 dan beìrbagai peìraturan peìrundang-undangan lainnya. Namun, koordinasi dan harmonisasi antara hukum adat dan hukum positif masih meìnjadi isu krusial, teìrutama dalam kasus-kasus yang meìlibatkan ranah pidana atau peìrdata yang leìbih luas. Reìkomeìndasi peìneìlitian Sanksi adat Passala eìfeìktif dalam meìnjaga keìarifan lokal dan sisteìm sosial masyarakat Ammatoa Kajang. Peìnting bagi peìmeìrintah dan peìmangku keìpeìntingan lainnya untuk leìbih meìmahami dan meìndukung keìbeìradaan sanksi adat ini, seìraya meìmastikan bahwa peìneìrapannya seìlaras deìngan prinsip-prinsip hak asasi manusia dan sisteìm hukum nasional. Peìneìlitian ini meìreìkomeìndasikan peìnguatan kolaborasi antara leìmbaga adat dan leìmbaga peìneìgak hukum formal untuk meìnciptakan sineìrgi dalam peìneìgakan hukum dan keadilan bagi masyarakat adat.